A comparison of the reading and math performance of Aral Kalinga (AK) and Non-Aral Kalinga students : implications for Aral Kalinga program improvement - BARBARA, ESGUERRA (Archīum Ateneo, 2011)
This study used the CIPP evaluation model of Daniel Stufflebeam to determine and compare the academic performance of four groups of students: Grades 2 and 3, Grades 4 and 5 AK and comparable non-AK students in Reading and Math to draw implications for AK